Respiratory function after 30+ years following sulfur mustard exposure in survivors in Sweden - Moradi, Faraidoun; Kjellberg, Sanna; Li, Ying; Daka, Bledar; Olin, Anna-Carin (Frontiers in Medicine, 2024)
Background: Sulfur mustard (SM) exposure causes acute and chronic respiratory diseases. The extent of small airway dysfunction (SAD) in individuals exposed to SM is unclear. This study evaluated and compared SAD in SM-exposed and SM-unexposed participants using noninvasive lung function tests assessing small airway function. Methods: This retrospective cohort study involved SM-exposed (n=15, mean age: 53±8 years) and SM-unexposed (n=15, mean age: 53±7 years) Kurdish-Swedish individuals in Sweden. Small airway resistance and reactance were assessed using impulse oscillometry (IOS). Nitrogen (N2) multiple breath washout (MBW) was employed to assess lung ventilation heterogeneity. The gas-exchanging capacity of the lungs was assessed using the diffusing capacity of the lungs for the carbon monoxide (DLCO) test. Lung function outcomes were reported as absolute values and z-scores. Group comparisons were performed using the Mann–Whitney U test. Results: No statistically significant differences in age, height, or body mass index were observed between the two groups. IOS showed significantly increased small airway resistance, while N2MBW exhibited significantly increased global and acinar ventilation heterogeneity in SM-exposed individuals compared to that in unexposed individuals. SAD was identified in 14 of 15 SM-exposed individuals, defined as at least one abnormal IOS difference between resistance at 5 and 20 Hz (R5-R20 and/or area of reactance (AX) or N2MBW lung´s acinar zone (Sacin), and DLCO adjusted to the alveolar volume (DLCO/VA) outcome. Of these 14 individuals, only five demonstrated concordant findings across the IOS and N2MBW tests. Conclusions: Exposure to SM was positively associated with long-term impairment of respiratory tract function in the small airways in the majority of the previously SM-exposed individuals in the present study. Furthermore, both IOS and N2MBW should be employed to detect SAD in SM-exposed survivors as they provide complementary information. Identifying and characterizing the remaining pathology of the small airways in survivors of SM exposure is a first step towards improved treatment and follow-up.